Human Umbilical Cord Wharton's Jelly Stem Cell Conditioned Medium Induces Tumoricidal Effects on Lymphoma Cells Through Hydrogen Peroxide Mediation. Issue 9 (11th February 2016) - Lin, Hao Daniel; Fong, Chui‐Yee; Biswas, Arijit; Choolani, Mahesh; Bongso, Ariff
ABSTRACT: Several groups have reported that human umbilical cord Wharton's jelly stem cells (hWJSCs) possess unique tumoricidal properties against many cancers. However, the exact mechanisms as to how hWJSCs inhibit tumor growth are not known. Recent evidence suggests that exposure of cancer cells to high hydrogen peroxide (H2 O2 ) levels from H2 O2 ‐releasing drugs causes their death. We therefore explored whether the tumoricidal effect of hWJSCs on lymphoma cells was mediated via H2 O2 . We first exposed lymphoma cells to six different molecular weight cut‐off (MWCO) concentrates of hWJSC‐conditioned medium (hWJSC‐CM) (3, 5, 10, 30, 50, 100 kDa) for 48 h. Since, the 3 kDa‐MWCO concentrate showed the greatest cell inhibition we then investigated whether the tumoricidal effect of the specific 3 kDa‐MWCO concentrate on two different lymphoma cell lines (Ramos and Toledo) was mediated via accumulation of H2 O2 . We used a battery of assays (MTT, propidium iodide, mitochondria membrane potential, apoptosis, cell cycle, oxidative stress enzymes, hydrogen peroxide, mitochondrial superoxide, hydroxyl radical, peroxynitrile anion, and lipid peroxidation) to test this mechanism. The hWJSC‐CM‐3 kDa MWCO concentrate significantly decreased cell viability and mitochondrial membrane potential and increased cell death and apoptosis in both lymphoma cell lines. There were significant increases in superoxide dismutase with concomitant decreases in glutathione peroxidase, catalase, and thioredoxin peroxidase activities. H2 O2 levels, mitochondrial superoxide, hydroxyl radical, peroxynitrile anion, and lipid peroxidation were also significantly increased in both lymphoma cell lines. The results suggested that the hWJSC‐CM‐3 kDa MWCO concentrate regulates cellular H2 O2 leading to a tumoricidal effect and may thus be a promising anti‐lymphoma agent. J. Cell. Biochem. 117: 2045–2055, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Several groups have reported that human umbilical cord Wharton's jelly stem cells (hWJSCs) possess unique tumoricidal properties against many ancers. We report that the 3 kDa‐MWCO concentrate of hWJSC‐conditioned medium inhibits the rowth of lymphoma cells and the tumoricidal effect was mediated via hydrogen peroxide signaling. The hWJSC‐CM‐3 kDa MWCO concentrate may thus be a promising anti‐lymphoma agent.